Therapeutic antibodies under development for SARS‐CoV‐2. Issue 2 (12th July 2021) - Ma, Zetong; Zhu, MengMei; Zhang, Shuyi; Qian, Kewen; Wang, Chuqi; Fu, Wenyan; Lei, Changhai; Hu, Shi
Abstract: The world is experiencing one of the most difficult moments in history with COVID‐19, which has rapidly developed into a worldwide pandemic with a significant health and economic burden. Efforts to fight the virus, including prevention and treatment, have never stopped. However, no specific drugs or treatments have yet been found. Antibody drugs have never been absent in epidemics such as SARS, MERS, HIV, Ebola, and so on in the past two decades. At present, while research on the SARS‐CoV‐2 vaccine is in full swing, antibody drugs are also receiving widespread attention. Several antibody drugs have successfully entered clinical trials and achieved impressive therapeutic effects. Here, we summarize the therapeutic antibodies against SARS‐CoV‐2, as well as the research using ACE2 recombinant protein or ACE2‐Ig fusion protein. Abstract : Several antibody drugs have successfully entered clinical trials and achieved impressive therapeutic effects. Due to the rapid progress in the field of therapeutic antibodies for COVID‐19 treatment, the authors summarize the neutralizing antibody drugs and fusion protein drugs that have attracted high attention at present, discuss the existing problems in the current application of antibodies drugs for COVID‐19, and prospect the future research direction in this field.